1998
DOI: 10.1074/jbc.273.39.25279
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Cross-linking of the Glycosylphosphatidylinositol-linked Protein CD59 on Hematopoietic Cells Induces Signaling Pathways Resembling Activation by Complement

Abstract: CD59 is a glycosylphosphatidylinositol-anchored cell surface glycoprotein involved in protecting cells from host-mediated complement attack. Studies have shown that antibody cross-linking of CD59 induces a series of intracellular signaling events including the activation of protein-tyrosine kinases (PTK). To further characterize these events, antibodies and complement 8, one of the natural ligands of CD59, were used to activate CD59. Antibody-induced cross-linking of CD59 on the surface of THP-1 and U937 hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 58 publications
0
52
0
5
Order By: Relevance
“…Signalling by a number of GPI-anchored proteins is mediated by Src kinase activation (Mouillet-Richard et al, 2000;Murray and Robbins, 1998;Wei et al, 2007). We investigated the role of Src in the Prod1 signalling cascade and found that the Src kinase inhibitor PP2 showed no inhibition of MMP9 induction when assayed by qRT-PCR (supplementary material Fig.…”
Section: Activation Of Erk1/2 and Egfr Signalling Is Implicated In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Signalling by a number of GPI-anchored proteins is mediated by Src kinase activation (Mouillet-Richard et al, 2000;Murray and Robbins, 1998;Wei et al, 2007). We investigated the role of Src in the Prod1 signalling cascade and found that the Src kinase inhibitor PP2 showed no inhibition of MMP9 induction when assayed by qRT-PCR (supplementary material Fig.…”
Section: Activation Of Erk1/2 and Egfr Signalling Is Implicated In MMmentioning
confidence: 99%
“…2A) upregulates MMP9 secretion in Prod1-transfected cells. We conclude that ERK1/2 and EGFR activation are significant components of the Prod1 response at the level of mRNA expression and subsequent protease secretion, but can only account for part of the MMP9-inducing activity.Signalling by a number of GPI-anchored proteins is mediated by Src kinase activation (Mouillet-Richard et al, 2000;Murray and Robbins, 1998;Wei et al, 2007). We investigated the role of Src in the Prod1 signalling cascade and found that the Src kinase inhibitor PP2 showed no inhibition of MMP9 induction when assayed by qRT-PCR (supplementary material Fig.…”
mentioning
confidence: 99%
“…Indeed, Western blot analysis with specific Abs against phosphotyrosine has become an accepted method to assess sperm capacitation (29,30,34). In other cell types, CD59 has been found to be physically connected to the membrane tyrosine phosphorylation machinery; if this were the case in sperm cells, CD59 could play a role in sperm capacitation (35)(36)(37). To investigate whether the absence of mCd59 could affect capacitation-dependent tyrosine phosphorylation and ionophore-induced acrosome reaction in mouse sperm, we analyzed both tyrosine phosphorylation and acrosome reaction in sperm obtained by the swim-out method from the epididymis of 3-moold mice.…”
Section: Normal Hormonal Levels and Capacitation-associated Tyrosine mentioning
confidence: 99%
“…In this study, we have found that anti-CRIT-ed1 blockage of the CRIT receptor increases the complement-mediated killing of two human myeloid cell lines (U937 and THP-1) and of monocytes. However, the relative contribution of CRIT to protecting against complement-dependent cytotoxicity in the THP-1 cells, for example, cannot be known, because certain other complement regulatory proteins are expressed, such as CD59 (40). Once C2 is bound to CRIT (unlike C2 bound to C4b), it cannot be cleaved by C1s to yield C2a and C2b and thus no longer partakes in C3 convertase formation.…”
Section: Discussionmentioning
confidence: 99%
“…If the dimerization of CRIT occurs through the formation of intermolecular disulfide bonds then candidate cysteine residues would be Cys 31,40,41 of TM1, Cys 69 of TM2, Cys 110 of TM3, or Cys 126,214,280 of the cytoplasmic tail. Disulfide linkages are not usually found in the cytoplasm because of the reducing environment there.…”
Section: Discussionmentioning
confidence: 99%